2020
DOI: 10.2196/17719
|View full text |Cite
|
Sign up to set email alerts
|

Use of Eye-Tracking Technology by Medical Students Taking the Objective Structured Clinical Examination: Descriptive Study

Abstract: Background The objective structured clinical examination (OSCE) is a test used throughout Spain to evaluate the clinical competencies, decision making, problem solving, and other skills of sixth-year medical students. Objective The main goal of this study is to explore the possible applications and utility of portable eye-tracking systems in the setting of the OSCE, particularly questions associated with attention and engagement. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…On the other hand, there are studies that have suggested the use of eye tracking (ocular metrics) to assess an objective evaluation in medical ( 24 , 25 ) and surgical education ( 2 , 17 , 26 , 27 ) and also in high-stakes assessment analogously to other validated objective evaluations, such as the Operative Performance Rating System, the Objective Structured Assessment of Technical Skills (OSATS) ( 3 ), or the Global Operative Assessment of Laparoscopic Skills (GOALS) ( 17 ). Eye tracking could serve to evaluate skills because this technology allows perceiving not only the pattern of gaze but also the frequency of fixation and the time of permanence, which are used as measures of the importance of the perceived stimulus, as well as pupil dilation, a marker of the effort and concentration of the subject ( 3 , 10 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are studies that have suggested the use of eye tracking (ocular metrics) to assess an objective evaluation in medical ( 24 , 25 ) and surgical education ( 2 , 17 , 26 , 27 ) and also in high-stakes assessment analogously to other validated objective evaluations, such as the Operative Performance Rating System, the Objective Structured Assessment of Technical Skills (OSATS) ( 3 ), or the Global Operative Assessment of Laparoscopic Skills (GOALS) ( 17 ). Eye tracking could serve to evaluate skills because this technology allows perceiving not only the pattern of gaze but also the frequency of fixation and the time of permanence, which are used as measures of the importance of the perceived stimulus, as well as pupil dilation, a marker of the effort and concentration of the subject ( 3 , 10 , 12 ).…”
Section: Discussionmentioning
confidence: 99%